Introduction to work and organizational psychology (Oxford ; Malden, Mass. : Blackwell, 2000)
This book is divided into five parts: Introduction; People at work; Human factors at work; Organizationas at work; and Issues for work and organizational psychology.
Keywords: Psychology; Organizational behavior; Psychology, Industrial -- Europe; Organizational behavior -- Europe